The Effect of School Principal Leadership, Discipline and Infrastructure on Teachers’ Performance in SMP Negeri Lempuing District, Ogan Komering Ilir Regency - Sari, Rizky Fajar; Wati , Sakdiah; Asiati, Diah Isnaini (International Journal of Marketing & Human Resource Research, 2024)
This research aims to determine 1) the influence of the principal's leadership, discipline, and infrastructure together on the performance of State Middle School teachers in Lempuing District, Ogan Komering Ilir Regency, 2) the influence of the principal's leadership, discipline, and infrastructure partially on the performance of State Middle School teachers in the District. Lempuing, Ogan Komering Ilir Regency. The type of research used is associative. The research uses leadership variables, work discipline, facilities, infrastructure, and performance. The research population was 218 State Middle School teachers in Lempuing District, Ogan Komering Ilir Regency. The sample was taken from 142 teachers using the Cluster sampling technique. The data required is player data with a retrieval method. Questionnaire data. The analysis technique used is multiple linear regression. The results of the research prove that: 1) there is a significant influence of leadership, discipline, and facilities and infrastructure on the performance of State Middle School teachers in Lempuing District, Ogan Komering Ilir Regency 2) there is a significant influence of leadership on the performance of Public Middle School teachers in Lempuing District, Ogan Komering Ilir Regency 3) there is an influence Discipline has a significant impact on the performance of State Middle School teachers in Lempuing District, Ogan Komering Ilir Regency. 4) Facilities and infrastructure have a significant influence on the performance of public middle school teachers in Lempuing District, Ogan Komering Ilir Regency